Do role models matter in large classes? New evidence on gender match effects in higher education - Stephan Maurer; Guido Schwerdt; Simon Wiederhold (Halle Institute for Economic Research (IWH), 2023)
It is well established that female students perform better when taught by female professors. However, little is known about the mechanisms explaining these gender match effects. Using administrative records from a German public university, which cover all programs and courses between 2006 and 2018, we show that gender match effects are sizable in smaller classes, but are absent in larger classes. These results suggest that direct and frequent interactions between students and professors are crucial for gender match effects to emerge. In contrast, the mere fact that one's professor is female is not sufficient to increase performance of female students.
Keywords: I21; I23; I24; J16; 330; gender gap; professors; role models; tertiary education